2019
DOI: 10.30845/ijbss.v10n11a15
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management, Top Management Demographics, Macro Environment and Organizational Performance: Evidence from Kenyan State-Owned Corporations

Abstract: This journal is a conceptualization of the relationship between Enterprise risk management, Top management demographics, Macro environment and performance. Some researchers have argued that Enterprise risk management influence performance positively whereas others have advanced that the influence is negative whereas others have contended that this strategic management practice is fairly recent, adopted to varying extent and its influence on performance is yet to be fully realized. There is also no agreement on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…Findings align with those of previous studies that highlighted the importance of ERM and its implementation, given its holistic and integrated view of business risk (Anton e Nucu, 2020;Bromiley et al, 2015;Hernandez-Madrigal et al, 2020). The current study's analysis also demonstrated that respondents identified top management support and organisational climate as ERM implementation determinants, akin to existing literature (Otieno et al, 2019;Trisnawati, Mustikawati & Sasongko, 2023;Yahaya & Yakubu, 2022). Furthermore, most respondents linked ERM implementation to improved business performance; such results are in line with previous studies as well (Annamalah et al, 2018;Fakir & Jusoh, 2020;Fauzi et al, 2022;Florio & Leoni, 2017;Gordon, Loeb & Tseng, 2009;Jonek-Kowalska, 2019;Mahama et al, 2022;Lukianchuk, 2015;Rehman & Anwar, 2019;Muralidhar, 2010;Naseem et al, 2020;Nugraha, Rizal & Ganika, 2022;Perera et al, 2020;Rauf, Jabarand & Mansor, 2020;Yudianto et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Findings align with those of previous studies that highlighted the importance of ERM and its implementation, given its holistic and integrated view of business risk (Anton e Nucu, 2020;Bromiley et al, 2015;Hernandez-Madrigal et al, 2020). The current study's analysis also demonstrated that respondents identified top management support and organisational climate as ERM implementation determinants, akin to existing literature (Otieno et al, 2019;Trisnawati, Mustikawati & Sasongko, 2023;Yahaya & Yakubu, 2022). Furthermore, most respondents linked ERM implementation to improved business performance; such results are in line with previous studies as well (Annamalah et al, 2018;Fakir & Jusoh, 2020;Fauzi et al, 2022;Florio & Leoni, 2017;Gordon, Loeb & Tseng, 2009;Jonek-Kowalska, 2019;Mahama et al, 2022;Lukianchuk, 2015;Rehman & Anwar, 2019;Muralidhar, 2010;Naseem et al, 2020;Nugraha, Rizal & Ganika, 2022;Perera et al, 2020;Rauf, Jabarand & Mansor, 2020;Yudianto et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…In terms of the relationship between respondents' demographic characteristics and their responses to commonly discussed ERM issues, the results of the present study are consistent with the findings of previous research. ERM issues were highly linked to respondents' educational level and job position; a finding confirmed by previous studies (Belas et al, 2023;Erin, Bamigboye & Arumona, 2020;Lamidi et al, 2022;Maharana et al, 2023;Odubuasi, Ofor & Ilechukwu, 2022;Otieno, Ogutu & Pokhariyal, 2019;Trisnawati, Mustikawati and Sasongko, 2023;Yahaya & Yakubu, 2022;Yang, Ishtiaq & Anwar, 2018).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…While the intervention was partial, the significant impact of ERM practices on this relationship emphasized the board's instrumental role in fostering effective risk management strategies that positively impacted overall organizational performance. Findings from previous studies by Otieno, Ogutu, and Pokhariyal (2019) and Girangwa, Rono, and Mose (2020) further supported the notion that the implementation of robust ERM practices had a positive and significant effect on organizational performance in government-owned entities, highlighting the importance of the board's involvement in driving improved performance through effective risk management practices.…”
Section: Summary Conclusion and Recommendations Summarysupporting
confidence: 64%
“…Ariffin and Kassim (2011) employed correlation analysis only to determine relationship between Basel banking supervision code practices and performance. Examples of studies which used multiple regression analysis include Laimaru (2018), Oruke et al (2020), Otieno, Ogutu and Pokhariyal (2019). Kobia and Mohamed (2006) investigated the effects of implementation of performance contracting in Kenyan public service and state corporations using non-quantitative approach.…”
Section: Statement Of the Problemmentioning
confidence: 99%